Public Relations and Media Role in Peace Building in Nigeria - Maiwada, Abdullahi Aliyu; Aondover, Perpetua Ogechi; Adewale, Olugbenga Charles; Falobi, Funmi; Onyejelem, Timothy Ekeledirichukwu (Budapest International Research and Critics University, 2025)
Public relations (PR) and media play crucial roles in peacebuilding in Nigeria, a nation with a diverse cultural, religious, and political landscape. In a country where ethno-religious conflicts, political tensions, and socio-economic disparities often lead to unrest, strategic PR and media efforts can foster dialogue, promote understanding, and build sustainable peace. The paper argues that PR professionals facilitate dialogue among conflicting parties by creating platforms for engagement, understanding, and negotiation. They design campaigns that promote mutual respect and tolerance. By sharing transparent and accurate information, PR efforts can bridge gaps between communities and institutions, fostering trust. PR and media are pivotal in shaping narratives, fostering dialogue, and building consensus in peacebuilding processes. By addressing challenges and adopting inclusive, transparent, and ethical approaches, these tools can significantly contribute to a more harmonious Nigeria. Conflicts are becoming more complex in more institutions and are involving multiple issues as well. Handling such conflicts enhance the client’s ability to function successfully in a volatile environment. In other words, more organizations have the potential for conflict that needs to be resolved than ever before. Skills are needed by public relations managers to evaluate the divergent interests of different groups to formulate alternatives that will satisfy the parties involved in the dispute. The paper concludes that PR and media work together to suppress divisive narratives by promoting content that emphasizes shared values and diversity. In times of unrest, PR teams communicate clear, accurate, and timely information to mitigate panic and prevent escalation. Media organizations must adopt conflict-sensitive reporting, avoiding sensationalism and inflammatory language.